Kewenangan Notaris Menyerahkan Sertipikat Pengurusan Balik Nama Yang Dimohonkan Oleh Pihak Lain (Studi Putusan Nomor 86/Pdt/2019/PT SMG) - Kumara, Prasetya Teja; Sudiarta, I Ketut (Acta Comitas, 2023)
This research aims to analyze the role of a notary in receiving certificates for changing names requested by other parties and the notary's authority to hand over certificates for changing names requested by other parties based on Decision Number 86/Pdt/2019/PT SMG. The research method used is juridical-normative. The results of the research show that the notary's authority to hand over a certificate of ownership that is submitted for transfer of name by a party who is not the owner of the property rights may not be exercised, because notaries generally have the authority to maintain the certificate for the purpose of executing the deed. A notary in carrying out his office must be careful when the certificate is handed over by someone who does not have rights to the land. When the person presenting the certificate is not the owner of the object, written authorization must be requested from the person submitting the certificate, or the notary may also request that the owner of the object and the third party recipient of the power of attorney appear simultaneously if there is an unwritten power of attorney.